Clinical management of a pituitary gland metastasis from clear cell renal cell carcinoma. Issue 7 (August 2018) - Di Nunno, Vincenzo; Mollica, Veronica; Corcioni, Beniamino; Fiorentino, Michelangelo; Nobili, Elisabetta; Schiavina, Riccardo; Golfieri, Rita; Brunocilla, Eugenio; Ardizzoni, Andrea; Massari, Francesco
Abstract : In very few years, several treatments have significantly improved the prognosis of patients with metastatic renal cell carcinoma (RCC). Despite this, the clinical outcomes of specific subgroups of patients including those with central nervous metastases still remain poor. In this population, a very infrequent and poorly described site of metastases is the pituitary gland. Because of the important endocrinal function and the anatomic site of this specific organ, clinical management of this complication requires several additional precautions compared with other central nervous metastases. Here, we describe a case of a single pituitary metastasis from clear cell RCC in a patient who showed a surprising progression-free survival and overall survival to sunitinib first-line treatment. Because of the uncommon clinical course of the disease of our patient and the atypical site of metastases, we want also to underline the importance of further investigation of molecular pathways associated with a favorable prognosis in patients with metastatic clear cell RCC.